Analisa Peran Kelembagaan Petani Terhadap Adopsi Sistem Pertanian Organik (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2024)
The purpose of this study is to analyze the role of farmer groups in the adoption of organic farming system innovations. The location of this research was carried out in the Argoayuningtani farmer group, Selo Boyolali. The research method used is descriptive quantitative and data analysis methods use the correlation coefficient The results of the data analysis obtained that the Learning Class Variable obtained an average Likert Scale of 4.29 (good), the Cooperation Vehicles Variable obtained an average of 4 (good), the Production Unit Variable obtained an average of 4.3 (good) and The Innovation Adoption Variable obtained an average Likert scale of 4.46 The significant value of the learning class variable is 0.000 <? 0.05. The cooperation vehicle variable is 0.197 > ? 0.05. The learning class variable is 0.000 < ? 0.05 which shows that there is a relationship between the role of farmer group production units on the adoption of organic farming system innovations. The R Square Determination Coefficient value is 0.965 or 96.5%, the effect of the role of the group on the adoption of organic farming system innovations, 3.5% is explained by other variables outside the learning class variables, collaboration vehicles and production units (good).